Thriving rough sets : 10th anniversary – honoring Professor Zdzisław Pawlak's life and legacy & 35 years of rough sets /: 10th anniversary – honoring Professor Zdzisław Pawlak's life and legacy & 35 years of rough sets. (2017) - Unknown
No abstract available